IMPACT OF 2017 AAP AND 2016 ESH GUIDELINES ON PAEDIATRIC HYPERTENSION PREVALENCE. (April 2021) - Fanelli, Elvira; Di Monaco, Silvia; Pappaccogli, Marco; Eula, Elisabetta; Fasano, Chiara; Masera, Guglielmo; Rabbone, Ivana; Rabbia, Franco; Veglio, Franco
Abstract: Objective: 2016 European Society Hypertension (ESH) and 2017 American Academy of Paediatrics (AAP) guidelines on hypertension in children and adolescents substantially diverge, for the first time, in the definition of hypertension. The aim of this study was to retrospectively assess the impact of the two different guidelines on prevalence of high blood pressure in a population of obese and normal-weight children and adolescents. Design and method: This study included an historical cohort of 624 subjects in age range 2–18 years, among referred to Paediatric Endocrinology Division and Hypertension Centre. They had previously undergone a blood pressure and anthropometric parameters measurement. Subjects were classified in normotensive, pre-hypertensive or hypertensive on the base of the latest ESH and AAP guidelines. Weight, height and body mass index (BMI) percentiles were considered according to age and gender. Subgroups by gender, BMI, age range were examined. Results: Mean age was 12 ± 3 years, with male accounting for 59% of population. According to 2017 AAP guidelines cut-offs, 204 subjects (32, 7%) were hypertensive, while only 110 subjects (17, 6%) were hypertensive according the 2016 ESH definition, with a statistical significance of difference observed (p < 0, 01). A higher proportion of hypertensive subjects when applied AAP nomograms was observed in all different subgroups for age, sex and BMI. However, the greater disagreement in the two classification was observed in aged less than 16 years of age and normal-weight subjects. Conclusions: AAP and ESH BP guidelines implies significant differences in BP classification in children and adolescent: with AAP nomograms application, excluding overweight subjects, a higher proportion of subjects were, and in the future will be, classified as hypertensive in all categories group.